DYNAMICS OF GENERATION Z SHARIA INVESTMENT DECISIONS : THE ROLE OF FINANCIAL LITERACY, INFLUENCERS, SOCIAL MEDIA AND RELIGIOSITY - Muhammad Rijalul Abror Al-Ma’ruf; Lailatul Qadariyah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
This research aims to identify the factors that influence Generation Z participation in Islamic investing. Given the significant increase of Islamic investors this study seeks to delve deeper into the roles of financial literacy, the influence of influencers and social media, and the aspect of religiosity as considerations in investment decision making. This qualitative research was conducted through in depth interviews with 10 Generation Z individuals in East Java province. The results show that financial literacy serves as the primary foundation in motivating Generation Z to engage in Islamic investing. Additionally, the influence of influencers and social media, as well as the awareness of the importance of managing finances in accordance with Islamic principles, are significant factors. These findings are expected to contribute to enhancing the financial literacy of Generation Z and serve as a basis for developing effective halal campaigns. By understanding the factors influencing Generation Z investment decisions Islamic capital market players can design products and marketing strategies that are suitable for increasing the number of Islamic investors in Indonesia.